Cross-cultural collaboration and cultural production within China's public museums: examining the challenges and practices guiding administration. Issue 3 (16th April 2023) - Chung, Carol; Manley, Andrew; Wang, Yi-Wen; Silk, Michael; Bailey, Rebecca
ABSTRACT: The transition from a centrally planned economy to a market economy with socialist characteristics has had a profound effect on China's cultural industries. This paper adopts a case study approach to illustrate the challenges that have shaped the administration of public museums as a consequence of China's economic reforms. By drawing upon an example of cross-cultural collaboration between Western cultural institutions and China's Nanjing Museum (南京博物院: nanjing bowuyuan ), we uncover the tensions that exist between China's cultural policy preferences and the encroaching values of the market economy. In doing so, this article contributes towards a richer exposition of the local practices guiding cultural management, reflecting the broader challenges endemic among China's cultural industries. Primarily, we seek to illustrate how market imperatives have influenced local practices, creating a context unique to China that deviates from the central tenets of neoliberal development and market management.